2013
DOI: 10.4103/0028-3886.115051
|View full text |Cite
|
Sign up to set email alerts
|

Complication avoidance and its management in endoscopic neurosurgery

Abstract: Endoscopic techniques are increasingly being used in recent times for various spinal and brain pathologies. Although endoscopic neurosurgical technique holds the potential for reducing morbidity, it is also associated with limitations such as steep learning curve, obstruction in manipulation of instruments by telescope in an already limited exposure, proximal blind spot, visual obscuration, disorientation, loss of stereoscopic image and others. Neuroendoscopy is distinct from micro-surgery and a thorough under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(62 citation statements)
references
References 11 publications
0
62
0
Order By: Relevance
“…Intra-ventricular bleeding can be caused by excessive side movements, removing the flexible scope in curved tip position, wrong entry in the lateral ventricle, injuries due to repeated introduction of endoscope without the use of the peel-away sheath or other sheath, direct ventricular access by the telescope, and the use of a sharp-edged sheath, etc. (59). Rarely blood might trickle from the burr-hole site into the ventricle.…”
Section: Intra-ventricular Bleedingmentioning
confidence: 99%
“…Intra-ventricular bleeding can be caused by excessive side movements, removing the flexible scope in curved tip position, wrong entry in the lateral ventricle, injuries due to repeated introduction of endoscope without the use of the peel-away sheath or other sheath, direct ventricular access by the telescope, and the use of a sharp-edged sheath, etc. (59). Rarely blood might trickle from the burr-hole site into the ventricle.…”
Section: Intra-ventricular Bleedingmentioning
confidence: 99%
“…During neuroendoscopy more often reported events are: Injury to the fornix, intraventricular hemorrhage, basilar artery injury, cardiac arrhythmias or respiratory arrest and failed ETV [28][29][30]. Our study reported the following complications: there were 4 cases of fever and meningeal irritation.…”
Section: Discussionmentioning
confidence: 71%
“…Camera, light source and image quality of the endoscopes needs to be checked before induction of anesthesia (26). Every single detail should be checked including side rod of table for holder attachment.…”
Section: █ Discussionmentioning
confidence: 99%